(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Chronic hepatitis B virus (HBV) infection is a significant risk factor for liver cirrhosis and hepatocellular carcinoma (HCC). Early detection and differentiation between malignant and benign liver lesions are crucial for timely management. Ultrasonography (USG) serves as a valuable non-invasive tool for liver lesion evaluation, particularly in resource-limited settings. Objective: This study aimed to evaluate the sonographic appearance of HCC and benign liver lesions in patients with chronic hepatitis B. Methods: This descriptive study was conducted at Jinnah Hospital, Lahore, over a period of four months. A total of 162 adult patients with diagnosed hepatitis B undergoing abdominal ultrasound were included using a convenience sampling technique. Data were collected on demographic details, liver lesion characteristics, liver margins, echotexture, ascites, and lesion location. Analysis was performed using SPSS version 24. Results: Among 162 patients, 129 (79.6%) were male and 33 (20.4%) females. Fever was reported in 94 (58%), and jaundice in 94 (58%) patients. Liver size was shrunken in 64 (39.5%), normal in 70 (43.2%), and enlarged in 28 (17.3%). Liver echotexture was coarse in 68 (42%), altered in 67 (41.4%), and homogeneous in 27 (16.7%). Ascites was present in 75 (46.3%) patients. HCC was diagnosed in 73 (38.8%), hepatic cysts in 63 (45%), and focal nodular hyperplasia (FNH) in 26 (16%). Conclusion: Sonographic evaluation effectively identified a range of liver pathologies in hepatitis B patients, with HCC being prevalent, especially in males and patients with cirrhotic features. Regular ultrasound surveillance in high-risk populations can facilitate early diagnosis and timely intervention.